2022
DOI: 10.1080/22221751.2022.2103456
|View full text |Cite
|
Sign up to set email alerts
|

Frequent convergence of mcr-9 and carbapenemase genes in Enterobacter cloacae complex driven by epidemic plasmids and host incompatibility

Abstract: Convergence of mcr and carbapenemase genes has been sporadically detected in Enterobacter cloacae complex (ECC) with an upward trend. However, the state of the epidemic and underlying mechanism of such convergence has been poorly understood. In this study, the co-occurrence of MCR and carbapenemases was systematically analyzed in 230 clinical ECC isolates collected between 2000 and 2018 together with a global dataset consisting of 3,559 ECC genomes compiled from Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Transconjugants with high colistin MIC were obtained when conjugating pCST17-2_1, indicating that mcr-9 was located on a self-transferable plasmid ( Table 2 ). This observation is consistent with previous reports that the worldwide dissemination of mcr-9 is mainly driven by HI2/HI2A plasmids ( 18 , 48 , 49 ). Furthermore, similar conjugative mcr-9 -carring plasmids have been found in food and clinical isolates in Japan ( 34 , 43 , 61 ), suggesting a One Health perspective on the transmission of such mcr homolog.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Transconjugants with high colistin MIC were obtained when conjugating pCST17-2_1, indicating that mcr-9 was located on a self-transferable plasmid ( Table 2 ). This observation is consistent with previous reports that the worldwide dissemination of mcr-9 is mainly driven by HI2/HI2A plasmids ( 18 , 48 , 49 ). Furthermore, similar conjugative mcr-9 -carring plasmids have been found in food and clinical isolates in Japan ( 34 , 43 , 61 ), suggesting a One Health perspective on the transmission of such mcr homolog.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple Enterobacterial species, including Salmonella ( 45 ), E. coli ( 45 ), E. asburiae ( 50 ), Citrobacter telavivum ( 51 ), and E. hormaechei ( 52 ) with the so-called qseBC genes, have been reported to exhibit colistin-susceptible phenotypes. In contrast, some other studies also found that lack of such a tandem system in certain bacterial species was associated with colistin-resistant phenotypes, as with E. roggenkampii ( 34 ), E. cloacae complex ( 48 ), and S . Newport ( 35 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…strains were found successively in different types of plasmids (IncFII, IncFIB, IncFIB, and IncFIA) [11] , [20] , [21] and different species, including E. cloacae , E. kobei , E. asburiae , E. ludwigii , and E. hormaechei [22] . Compared to mcr-10 , mcr-9 has a higher isolation rate from conserved plasmid types (IncHI2/2 A) in ECC strains and usually coexisted with carbapenemase genes [18] . Moreover, in a recent report, mcr-9 was co-transferred with bla NDM-1 among ECC strains, although transconjugants did not show resistance to colistin [23] .…”
Section: Introductionmentioning
confidence: 99%
“…E. asburiae is widely isolated throughout the United States due to the horizontal transfer of bla IMI-2 carbapenemase gene between clinical and river environments [17] . A study collected mcr-9/10 positive E. asburiae showed that sequence type (ST) 484 mcr-9 -carrying E. asburiae strains were dominant (29.4%, 10/34) [18] . Besides, ST252 E. asburiae was reported as the predominant reservoir of a new transferable quinolone resistance qnrE family allele gene qnr Eas1 [19] .…”
Section: Introductionmentioning
confidence: 99%